(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2025)
Background: The hospitality industry, a major contributor to global environmental issues, is under increasing pressure to adopt sustainable practices. While the concept of sustainability has gained momentum worldwide, the extent of its adoption in emerging urban centres like Kolkata remains unclear. Objective: The objectives are to explore and implement innovative waste management technology and practices in Kolkata star hotels to reduce environment impact and maximize resource recovery, where also identify and addressing the barriers hindering their adoption to promote sustainable waste management in hospitality sector. Methodology: This study explored sustainable waste management practices in five stars hotels in Kolkata. In-depth interviews and focus group discussions with supervisory staff from renowned hotel chain were done. The research adopted a qualitative design, with a total sample size of 30 participants. Data was analysed thematically to identify trends. Results: Kolkata’s hotel industry faces challenges in sustainable waste management due to financial constraints, technological limitations, infrastructure gaps, and guest behaviour. Progress has been made through waste segregation, plastic reduction, and digital tools. Overcoming these challenges requires government support, technological advancements, community engagement, and behavioural change programs. By integrating waste reduction, recycling, and resource recovery, hotels can establish a sustainable circular economy model. Conclusion: Continuous monitoring, innovation, and collaboration are circular for long-term success.